CODES OF CONDUCT OF PHARMACEUTICAL COMPANIES AS ACTS OF AUTONOMOUS LAW AND THEIR PLACE WITHIN FULLER’S MORAL SCALE - Danilovic, Jelena (Pravni zapisi, 2021)
The article analyses codes of conduct of pharmaceutical companies, as specific autonomous acts which prescribe both moral principles of fair and honest business and particular legal duties. Article aims to set jurisprudential base for better understanding of this concept. The first part of the article deals with development and specifics of ethical codes as hybrid, legal and moral instruments. The second part analyses legal nature of the codes reviewed from pluralistic jurisprudence stance, identifying them as institutes of autonomous law. The third part analyzes moral content of codes, while in the final part the article analyzes these specific legal and moral institutes, within the context of Fuller’s moral scale. Applied methods are conceptual analysis of the code of conduct concept as well as descriptive analysis of the business practice and available, relevant autonomous rules. Overview includes also comparative method of presentation of empirical practice. Conclusion analyses position of ethical codes, as specific autonomous acts, within the frame of Fuller’s moral scale and perceived antagonism of morality of aspiration and morality of duty.